PENGARUH TINGKAT PENGANGGURAN, INVESTASI, PENDIDIKAN TERHADAP KEMISKINAN DI KABUPATEN/KOTA PROVINSI BANTEN - Vera Ainunnisa; Wahyu Hidayat Riyanto (Program Studi Ekonomi Pembangunan, 2019)
Poverty is one of the fundamental problems that is the center of attention of governments in any country not least in developing countries, namely Indonesia. One important aspect in supporting poverty reduction strategies is the availability of accurate and targeted poverty data. Poverty is caused by various factors, namely slow economic growth, investment levels that are still below standard, low levels of education and high levels of unemployment. This study aims to determine the effect of unemployment, investment and education on poverty in Banten Province. The method used is panel data regression analysis. The results show that unemployment has a positive and significant effect with a coefficient value of 0.173297 and a probability value of 0.0005, investment has a positive and insignificant effect with a coefficient of 0.005261 and a probability value of 0.4127, while education has a negative and significant effect with a coefficient of -0.290174 with a probability value of 0.0147 on poverty in Regency / City of Banten Province. And simultaneously unemployment, investment and education variables affect poverty in the Regency / City of Banten Province.